Limb salvage in osteosarcoma using autoclaved tumor-bearing bone - Kok Long, Pan; Wai Hoong, Chan; Gek Bee, Ong; Shanmugam, Premsenthil; Mohammad, Zulkarnaen; Dayangku, Norlida; Zainal, Abidin (BioMed Central Ltd., 2012)
Kok Long Pan, Wai Hoong Chan, Gek Bee Ong, Shanmugam Premsenthil, Mohammad Zulkarnaen, Dayangku Norlida and Zainal Abidin